Floral MADS‐box protein interactions in the early diverging angiosperm Aristolochia fimbriata Cham. (Aristolochiaceae: Piperales). Issue 2 (8th February 2019) - Peréz‐Mesa, Pablo; Suárez‐Baron, Harold; Ambrose, Barbara A.; González, Favio; Pabón‐Mora, Natalia
Abstract : Floral identity MADS‐box A, B, C, D, E, and AGL6 class genes are predominantly single copy in Magnoliids, and predate the whole genome duplication (WGD) events in monocots and eudicots. By comparison with the model species Arabidopsis thaliana, the expression patterns of B‐, C‐, and D‐class genes in stamen, carpel, and ovules are conserved in Aristolochia fimbriata, whereas A‐, E‐class, and AGL6 genes have different expression patterns. Nevertheless, the interactions of these proteins that act through multimeric complexes remain poorly known in early divergent angiosperms. This study evaluates protein interactions among all floral MADS‐box A. fimbriata proteins using the Yeast Two Hybrid System (Y2H). We found no homodimers and less heterodimers formed by AfimFUL when compared to AfimAGL6, which allowed us to suggest AGL6 homodimers in combination with AfimSEP2 as the most likely tetramer in sepal identity. We found AfimAP3‐AfimPI obligate heterodimers and AfimAG‐AfimSEP2 protein interactions intact suggesting conserved stamen and carpel tetrameric complexes in A. fimbriata . We observed a broader interaction partner set for AfimSEP2 than for its paralog AfimSEP1. We show conserved and exclusive MADS‐box protein interactions in A. fimbriata in comparison with other eudicot and monocot model species in order to establish plesiomorphic MADS‐box protein floral networks in angiosperms.